Pengaruh Multiple Damages Struktur Kapal Berbahan Sandwich Panel Menggunakan Respon Getaran - Windra Iswidodo; Anauta Lungiding Angga Risdianto (Techno Bahari, 2020)
Nowadays, there are a lot of new breakthroughs in material technology. One of the them is the use of Sandwich panel Material. Sandwich panel is a material that consist of two steel plates separated by a core part. On its application on ship, Sandwich panel will get repetitive force from the outside. This research will identify multiple damages with vibration characteristic approach with the experimental method and finite element analysis. Effect of defect on Sandwich Panel core material based on the experimental result is a decrease in natural frequency means of 1.64 percent.